The Impact of Nutritional and Dietary Factors on Hashimoto’s Thyroiditis: A Comprehensive Review - Rybka, Zuzanna; Kamińska, Monika; Moczyróg, Katarzyna; Karnas-Bogacka, Patrycja; Uchto, Adrian; Dąbrowska, Natalia; Marszałek-Moc, Kaja; Miernik-Skrzypczak, Magdalena; Jasiewicz, Maria; Palacz, Karolina Alicja (Quality in Sport, 2024)
Introduction. Hashimoto’s disease (HD) is the main cause of hypothyroidism in countries where there is no iodine deficiency in the diet. Characteristic antibodies for it are anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) and their level positively correlates with the severity of HD. Whereas its occurrence is related to genetic, environmental and existential factors. Aim of study. The aim of this study was to analyze dietary factors (protein, fat, vitamin D, iodine, selenium, gluten) and intestinal microbiota on the risk of developing Hashimoto’s disease and the influence of each of these factors on its course. Materials and methods. More than 90 articles addressing these issues were analyzed. They were found using the PubMed search engine, and the time frame of these publications covered the last 10 years. Results. Excess iodine is the most important environmental factor influencing the development of Hashimoto’s disease. Also, selenium deficiency contributes to the development of HD. On the other hand, the concentration of vitamin D is lower in patients with Hashimoto’s disease than in the general population. Furthermore, Vitamin D supplementation reduces the concentration of anti-Tg antibodies. In addition, different types of dietary fat affect thyroid hormone levels differently and a deficiency of protein in the diet causes an increase in TSH and a decrease in thyroid hormones. Moreover, changes in the gut microbiome have been observed in people suffering from Hashimoto’s disease. Conclusions. The risk of developing Hashimoto’s disease can be increased and decreased by diet and diet allows for the modification of hormone levels in the hypothalamus-pituitary-thyroid axis.